Toxicity and physiological effect of quercetin on generalist herbivore, Spodoptera litura Fab. and a non-target earthworm Eisenia fetida Savigny. (December 2016) - Selin-Rani, Selvaraj; Senthil-Nathan, Sengottayan; Thanigaivel, Annamalai; Vasantha-Srinivasan, Prabhakaran; Edwin, Edward-Sam; Ponsankar, Athirstam; Lija-Escaline, Jalasteen; Kalaivani, Kandaswamy; Abdel-Megeed, Ahmed; Hunter, Wayne B.; Alessandro, Rocco T.
Abstract: A novel flavonoid, quercetin, was isolated from the medicinal plant Euphorbia hirta L. through chromatography techniques including: TLC, Column chromatography, NMR and then screened for toxicity to larvae of Spodoptera litura Fab. Bioassays were used to analyze pupal weight, survival rate, fecundity, egg hatchability, population growth index, Nutritional index and histopathology of treated larvae at a range of E. hirta extract concentrations. Results of toxicity assays demonstrated that, 6 ppm of quercetin caused 94.6% mortality of second, 91.8% of third, 88% of fourth, and 85.2% of fifth instars respectively. The lethal concentrations (LC50 and LC90 ) was calculated as 10.88 and 69.91 ppm for fourth instar larvae. The changes in consumption ratio and approximate digestibility produced a reduction in growth rates. Histopathology examinations revealed that the cell organelles were severely infected. Analyses of earthworm toxicity effects resulted in significantly lower rates compared to synthetic insecticides (chloropyrifos and cypermethrin). These results suggests that the botanical compound (quercetin), could have a part as a new biorational product which provides an ecofriendly alternative. Validation of the potential of quercetin, still needs to be demonstrated under field conditions, where formulation will be important in maintaining the activity. Graphical abstract: Highlights: Important chemical compound with pesticidal activity was identified from Euphorbia hirta L. extract as quercetin. Survival, food utilization and cell organelles of S. litura was negatively affected after treatment with quercetin. The effect of quercetin on earthworm was non-significant when compared with monotrophos and cypermethrin.